FREEDOM OF CONSCIENCE, OPINION AND FREEDOM OF RELIGION BELIEFS - A RIGHT OF PERSONS DEPRIVED OF THEIR LIBERTY - Nicoleta Georgeta VASILE (CONSTANTINESCU) (Challenges of the Knowledge Society)
This article represents an analysis of the manner in which the freedom of conscience, freedom of opinions and freedom of religion of inmates are respected, with a particular analysis made on a Romanian prison. In this study I referred to the jurisprudence of the ECtHR in cases against Romania, the national legislation governing the rights of detainees, the collaboration between religious organizations and prisons in order to respect the right to religious freedom, the impact of respecting this right on behavior, the impact of re-educating inmates.